Favard – Amerio theory for almost periodic functional-differential equations without the use of $H$-classes of these equations - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
The Favard – Amerio theory is constructed for almost periodic functional-differential equations in a Banach space withoutthe use of $\scr H$ -classes of these equations. For linear equations, we present the first example of an almost periodic operator,which has no analogs in the classical Favard – Amerio theory.